Analysing the efficiency of renewable energy consumption among oil‐producing African countries. (September 2016) - Ackah, Ishmael; Alabi, Oluwafisayo; Lartey, Abraham
Abstract: Africa's growth over the past two decades has been unprecedented. However, access to modern forms of energy seems to be a major hurdle for most African countries even though renewable energy sources abound. It has been argued that, knowledge of demand determinants and estimates help to guide investment and policy design in the energy industry. This study therefore examined the efficiency of renewable energy consumption. Furthermore, it investigated the effect of carbon emissions, GDP per capita, energy resource depletion and human capital development on renewable energy demand in 10 African countries. A dynamic panel generalised method of moments, panel fixed‐effect and a panel random‐effect models were applied. The results suggest that economic growth, energy prices, carbon emissions and energy resource depletion significantly affect renewable energy demand in one or all the models. The study recommends that to promote renewable energy consumption, economic welfare of the population should be enhanced.